BIOCOMPATIBILITY OF ENDOGENOUS AND LACTOBACILLUS PROBIOTIC STRAINS IN THE EXPERIMENT - Lavryk, G.S. (World of Medicine and Biology, 2016)
Antibiotic-associated intestinal dysbacteriosis was modeled during a three-day experiment on white mice. The complete elimination of Escherichia coli and Bifidobacterium spp, significant reduction in the number of Lactobacillus spp. and the prolieration of fungi of the genus Candida spp. were recorded. After the implantation of lactobacilli, a low efficiency in microflora correction was found using auto strains in comparison to the probiotics. During 26-day self- ealing period after the beginning of the experiment, the gradual mplementation of the initial quantitative indicators of Lactobacillus spp. was made in the ontrol group and in the group with the use of autostrains, which significantly exceled the level of lactobacilli in the groups that used probiotic strains of lactic acid bacteria.
Keywords: lactobacilli; conditionally pathogenic microorganisms; dysbacteriosis; Lactobacterin (probiotic); biocorrection